Impact of surgical volume and surgical outcome assessing registers on the quality of thyroid surgery. Issue 4 (August 2019) - Patel, Neil; Scott-Coombes, David
Abstract : The available evidence concerning the relationship between volume and outcome for thyroid surgery is assessed in this article. Morbidity forms the principal surrogate marker of thyroid surgery quality for which postoperative hypocalcaemia and recurrent laryngeal nerve injuries are most commonly reported upon. Whilst there is an abundance of published data for these outcomes, interpretation to recommend annual volume thresholds is challenging. This is due to a lack of consensus on definitions not only for outcomes but high and low volume surgeons. The evidence reviewed in this article supports the notion that high volume surgeons achieve superior outcomes in thyroid surgery quality though it is not possible to recommend minimal annual volumes on the basis of this evidence alone. Every thyroid surgeon should know their own outcomes and how they compare with their peers and engagement in thyroid surgery registries can facilitate this.